Eco-friendly encapsulation: Investigating plant-based protein-alginate shells for efficient delivery and digestion of hemp seed oil encapsulated via supercritical CO2 dispersion - Gholivand, Somayeh; Tan, Tai Boon; Yusoff, Masni Mat; Qoms, Mohammed S.; Wang, Yong; Liu, Yuanfa; Nyam, Kar Lin; Tan, Chin Ping (Elsevier Ltd, 2025)
In this study, supercritical carbon dioxide solution-enhanced dispersion (SEDS) was used to encapsulate hemp seed oil (HSO) within matrices of hemp seed protein isolate (HPI), pea protein (PPI) and soy protein (SPI) (0.5 % w/v) in complex with alginate (AL) (0.01 % w/v). The effects of different pH levels (3–9), NaCl concentrations (0–200 mmol/L) and simulated gastrointestinal conditions on HSO release and digestion patterns were analyzed. The findings revealed that SPI/AL microcapsules effectively maintained structural integrity and controlled oil release across diverse pH levels and salt concentrations. During gastrointestinal phases, minimal oil release was observed during oral digestion (<25 % for all samples), while significant (P < 0.05) gastric release occurred in PPI/AL (55.4 %) and SPI/AL (78.1 %) microcapsules. Surprisingly, HPI/AL microcapsules exhibited delayed and sustained release (27.9 %), indicating their potential as ideal wall material for delivering sensitive food and pharmaceutical ingredients to the intestinal stage while minimizing damage in the harsh gastric environment.